Evaluating Government Roles in Traditional Market Development: A Case Study of Paya Ilang Market, Aceh Tengah - Ashwad, Hajar; Teniro, Alwin; Zunafriesma, Nanda; Effendi, Muhsin; Safrida, Viana (Pencerah, 2024)
The arrangement of the Paya Ilang Traditional Market in Central Aceh Regency aims to organize trading activities within the designated market building. However, this initiative faces challenges as vendors are reluctant to use the provided facilities, leaving the market building vacant and poorly maintained. This study seeks to evaluate the role of local government in the development and enhancement of traditional markets and to identify factors influencing the success of market regulation. A qualitative approach was employed, incorporating in-depth interviews, field observations, and analysis of relevant documents. The findings reveal several critical issues, including ineffective communication between the government and vendors, unsuitable market building conditions (such as inadequate lighting and ventilation), and a lack of strict enforcement of regulations. Additionally, limited access roads and insufficient parking space exacerbate the problems. The study concludes that renovating the market building with active involvement from vendors is crucial to achieving mutual understanding. The government must improve communication, provide clear guidance, and enforce regulations rigorously to raise vendor awareness of the importance of cleanliness, comfort, and public order. Market revitalization is anticipated to address these challenges while enhancing the market’s appeal as a modern and orderly trading hub.